Analytical Critique of “Contemporary Arabic Poetry, Its Issues and Its Artistic and Technical Aspects Translated by “Sayyedhosein Sayyedi” - Mohammad Rahimi Khoygani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The translation critique has its place in the scientific community in our contemporary world, since the correct criticism corrects and revises the translation and makes a clear mirror for the translator to see the pros and cons of his work, Because of this place, the present paper seeks to provide a critical analysis of Sayyed Hosein Sayyedis translation Entitled ““Contemporary Arabic Poetry, Its Issues and Its Artistic and Moral Phenomena”   that is compiled by “Ezzoddin Ismaeil”.  This critical analysis is based on the descriptive analytical approach, divided into two parts, a section dealing with content, and we are concerned in this section with the original text because the translation did not benefit us, and the other section deals with how to translate in terms of meaning and structure. The results of this research show that the issues of the book are both comprehensive and fresh book although it was published years ago. Besides,   it has some flaws in the research methodology. Additionally, in terms of translation, the book is full of translation errors and semantic errors, especially in the translation of poems.